Radio Detection of the Sun - Anh, Pham Tuan; Thieu, Dang Quang; Diep, Pham Ngoc; Dong, Pham Ngoc; Hiep, Nguyen Van; Hoai, Do Thi; Nhung, Pham Thi Tuyet; Thao, Do Thi; Darriulat, Pierrer (Communications in Physics, 2011)
The radio emission of the Sun has been measured using a radio interferometer including two Yagi antennas operated at 610 MHz. We report the observation of interferences and comment on the results.